Assessment of Renewable Energy Technology and a Case of Sustainable Energy in Mobile Telecommunication Sector - Michael S. Okundamiya; Joy O. Emagbetere; Emmanuel A. Ogujor (The Scientific World Journal)
The rapid growth of the mobile telecommunication sectors of many emerging countries creates a number of problems such as network congestion and poor service delivery for network operators. This results primarily from the lack of a reliable and cost-effective power solution within such regions. This study presents a comprehensive review of the underlying principles of the renewable energy technology (RET) with the objective of ensuring a reliable and cost-effective energy solution for a sustainable development in the emerging world. The grid-connected hybrid renewable energy system incorporating a power conversion and battery storage unit has been proposed based on the availability, dynamism, and technoeconomic viability of energy resources within the region. The proposed system’s performance validation applied a simulation model developed in MATLAB, using a practical load data for different locations with varying climatic conditions in Nigeria. Results indicate that, apart from being environmentally friendly, the increase in the overall energy throughput of about 4 kWh/$ of the proposed system would not only improve the quality of mobile services, by making the operations of GSM base stations more reliable and cost effective, but also better the living standards of the host communities.